Combined effect of size-reduction equipment-screw press on extractability of oil and protein by wet processing of coconut - Gonzales, Antonia L.; Buccat, Elinor F.; Mañalac, Guillermina C. (1981)
This study is a follow-uo, in bench scale , of the findings under laboratory conditions regarding the extraction of oil and protein form coconut meas of various particles sizes. Four different grinder-press combinations were compared in terms of percent oil and protein extracted ; also in terms of percent of skim milk and solid recovered. Time and power spent were incidentally recorded. The best particle size of oil and protein extraction was found to be mesh size 40.10. This was obtained by grinding the meat in a colloid mill. In bench scale , the best conditions for extraction were : slurrying for fifteen minutes; water-to-meat ratio of 0.25:1; and two pressings in a hander expeller. The percentage of oil extracted was 85.24 and that of protein, 78.7.